The effects of cooperative games on young learners' English vocabulary learning achievement and their retention - Trần Thị Mai Lan (Trường Đại học Trà Vinh, 2022)
Given very scarce research on the effects of cooperative games on young learners’ English vocabulary learning achievement and their retention in Vietnam and some problems relevant to teaching and learning English Vocabulary at Tran Van An primary school in Tra Vinh city, this research is constructed to provide insights into the local context. The thesis sets out to achieve two main aims. The first objective is to investigate the effects of cooperative games on young learners’ English vocabulary learning achievement and their retention. The second objective is to explore young learners’ attitudes about learning English vocabulary through cooperative games.